The Utilization of Agricultural Mechanization and Its Impact on Integrated Rice Farming and Cattle Farming in Merauke Regency - T. A. K Rimbayana; Abdul Rizal; Wa Ode Suriani; Natsir Sandiah; Yosehi Mekiuw; Yus Witdarko (Journal of Agriculture, Agribusiness, Welfare, Technology, Humanity, Environment, Social, and Economy, 2026)
Agricultural mechanization is an important strategy for increasing the efficiency and productivity of integrated rice farming with cattle farming in Merauke Regency. Agricultural mechanization can improve labor efficiency and accelerate the cultivation process, from land preparation to post-harvest. This research was conducted from October to December 2025 in three districts: Tanah Miring, Kurik, and Semangga. The research locations were selected based on the highest rice production centers in Merauke Regency. Data in this study were obtained from primary and secondary data. The results showed that all rice farmers who are members of farmer groups have utilized agricultural machinery in their farming processes, including cultivation, harvesting, and post-harvest. Rice farming using mechanization is feasible with a R/C ratio of 2.38. The amount of farmer income is Rp 32,590,000 and profit is Rp 21,907,000 per planting season.